2016
DOI: 10.1152/ajpregu.00298.2016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic pathways of lung inflammation revealed by high-resolution metabolomics (HRM) of H1N1 influenza virus infection in mice

Abstract: Influenza is a significant health concern worldwide. Viral infection induces local and systemic activation of the immune system causing attendant changes in metabolism. High-resolution metabolomics (HRM) uses advanced mass spectrometry and computational methods to measure thousands of metabolites inclusive of most metabolic pathways. We used HRM to identify metabolic pathways and clusters of association related to inflammatory cytokines in lungs of mice with H1N1 influenza virus infection. Infected mice showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
102
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 65 publications
12
102
0
Order By: Relevance
“…increased. These findings are consistent with the outcomes of viral infection [39][40][41], suggesting that AFB 1 exacerbated viral infection. In addition, levels of 20 and 40 µg/kg AFB 1 also increased lung injury and inflammatory cell infiltration in SIV-infected mice.…”
Section: Afb 1 Promotes Siv Infection Through Inducing a Switch In Pasupporting
confidence: 83%
“…increased. These findings are consistent with the outcomes of viral infection [39][40][41], suggesting that AFB 1 exacerbated viral infection. In addition, levels of 20 and 40 µg/kg AFB 1 also increased lung injury and inflammatory cell infiltration in SIV-infected mice.…”
Section: Afb 1 Promotes Siv Infection Through Inducing a Switch In Pasupporting
confidence: 83%
“…IAV cause severe respiratory tract infections, which are associated with lung inflammation, excessive ROS production from NOX2 oxidase and significant lung pathology . The spatial restrictions of ROS strongly suggest that their site of production governs their site of action.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, induction of mTORC1 signaling by the influenza virus leads to higher usage of essential amino acid storages for concurrent production of large amounts of viral and cellular proteins. Infection of influenza virus can also alter the cellular level and metabolism of purines and pyrimidines [8,98,100], and is associated with both increased activities of nucleotide catabolism core enzymes including adenosine deaminase (ADA) and xanthine oxidase (XO) and elevated levels of inosine, hypoxanthine, xanthine, and uric acid in serum and bronchoalveolar lavage fluid. Enhanced catabolic degradation of nucleotides and their metabolites can facilitate the production of superoxide and contribute to the pathogenesis of influenza infection [23].…”
Section: Other Metabolitesmentioning
confidence: 99%
“…Results of a published study showed that the replication of the influenza virus depends on host cellular metabolism such that metabolites including nucleic acids, proteins, glycoproteins, and lipids are crucially required for the life cycle of the influenza virus [7]. Recent research on a mouse model showed that influenza infection could affect more than 100 metabolite markers in serum, lung, and bronchoalveolar lavage fluid [8]. Acquiring the required materials from the host cell to self-replicate, the virus can disrupt biochemical processes such as glycolysis, fatty acid (FA) synthesis, and glutamine pathways [9].…”
Section: Introductionmentioning
confidence: 99%